Unveiling Nepal’s Hydro-Climatic Diversity: A Comprehensive Study from East to West - Bhattarai , Bikas Chandra (Journal of Hydrology and Meteorology, 2024)
This study delves into the comprehensive analysis of temperature, precipitation, and wind patterns across four distinct blocks in Nepal, shedding light on regional climate variations. Examining a 30-year (1990 – 2020) dataset, temperature variations reveal the East: Block 1 consistently experiencing higher average temperatures. Findings align with existing research, emphasizing local geographical features influence on temperature gradients. The precipitation analysis indicates the Block 1 receives the highest rainfall, correlating with established monsoon patterns. Western regions (Block 3) transition to arid climates, influenced by its most area in rain shadow effect of the Himalayas. Regression analysis reveals a warming trend in all blocks, reinforcing global climate change impacts. Precipitation trends exhibit nuances, with the East and Centre (Block 2) experiencing increases, while the Block 4 shows a decreasing trend. Extreme precipitation values highlight spatial variability, crucial for climate adaptation strategies. The study extends to extreme wind analysis, showcasing distinct patterns in each block, providing insights into potential risks. Wind direction analysis reveals unique patterns, contributing to a holistic understanding of regional climate dynamics. These findings contribute to the scientific discourse on climate resilience, emphasizing the need for tailored strategies in diverse geographical contexts.